Gestión de talento humano del Gobierno Autonomo Descentralizado Parroquial Rural de Febres Cordero periodo 2022. - Caravedo León, Jennyffer Estefanía (2023)
In the present case study, the management of human talent of the Decentralized Autonomous Rural Parish Government of Febres Cordero was evaluated in the period 2022, in order to determine the main training needs of personnel within the Department of Human Talent. For this, an approximation methodology was used, with a descriptive, correlational and exploratory research model, using collection techniques such as the survey and interview, where the survey was applied to the head of talent management and the interview to the heads of the four departments of the institution. The results indicated that the talent management carried out in the GADPR of Febres Cordero lacks symmetry, as it was concluded that training is not being conducted annually and the selection and recruitment process is not effective as it should be, for this reason policies for recruitment are recommended to encourage job meritocracy and guidelines are given for designing a continuing training programme.